Oral Submucous Fibrosis (OSMF) : A study of 101 cases - J V Tupkari; J D Bhavthankar; M S Mandate (Wolters Kluwer Medknow Publications, 2007)
Oral submucous fibrosis is a clinically well-established condition. The prevalence rate ranging from 0.2% to 0.5%, with a known malignant potential. Extensive research has been carried out by various researchers in different parts of the country to study various aspects of the disease. However, to the best of our knowledge no such study has so far been carried out in Marathwada Region of Maharashtra. Hence it was decided to carry out a clinical study of oral submucous fibrosis patients reporting at Government Dental College and Hospital, Aurangabad, to find out the clinical pattern of presentation and various associated habits prevailing in this region. The study showed male preponderance affecting individuals in second and third decades of life. All the patients had the habit of chewing betel leaves, betel nuts, tobacco, gutkha, alone or in various combinations. The associated causative factors were high chilli intake, nutritional deficiencies, and the clinical features were varied such as burning sensation, intolerance to spicy food, restricted mouth opening and difficulty in speech and deglutition. Histopathology was the characteristic of OSMF and was consistent with clinical grades of the disease but could not be corelated to the degree of mouth opening. The study of 101 cases of oral submucous fibrosis is reported.